Institutional Quality and Tax Revenue in CÃ´te d’Ivoire: Evidence from ARDL Approach - Soro, Siongofolo Seydou (International Journal of Economics and Financial Issues, 2020)
In this paper, we examine the main determinants of tax revenues in CÃ´te d’Ivoire, paying attention to institutional factors and the informal economy. To do this, we apply the autoregressive distributed lag model developed by Pesaran et al. (2001) on annual data covering the period 1984-2016. The results show that the low quality of institutions and the high share of the informal economy are among the factors explaining the low mobilization of tax revenues in CÃ´te d’Ivoire. The results also reveal that GDP per capita, official development assistance, the share of services in GDP, the distribution of income within the population and the education level of the population positively affect tax revenues. On the other hand, trade openness negatively affects tax revenues. Based on these results, the paper provides several recommendations that can help improve tax revenues in CÃ´te d’Ivoire. Keywords: Tax revenue, Institutional quality, Informal economy, Cointegration, CÃ´te d´Ivoire. JEL Classifications: H2, O17 DOI: https://doi.org/10.32479/ijefi.10363